2008
DOI: 10.1152/japplphysiol.00069.2007
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter blood flow change is unevenly distributed during moderate isocapnic hypoxia in humans

Abstract: Hypoxia increases cerebral blood flow (CBF), but it is unknown whether this increase is uniform across all brain regions. We used H(2)(15)O positron emission tomography imaging to measure absolute blood flow in 50 regions of interest across the human brain (n = 5) during normoxia and moderate hypoxia. Pco(2) was kept constant ( approximately 44 Torr) throughout the study to avoid decreases in CBF associated with the hypocapnia that normally occurs with hypoxia. Breathing was controlled by mechanical ventilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 44 publications
5
100
2
Order By: Relevance
“…Regarding absolute intensity, exercise test ended earlier under hypoxic than normoxic conditions (decrease of about 19.1%) as expected [4,27]. After adjusting the data to the last three exercise stages respectively for both conditions instead of regarding absolute intensity levels, heart rate, lactate concentration and ratings of perceived exertion did not differ between conditions.…”
Section: Heart Rate Lactate Concentration and Ratings Of Perceived Esupporting
confidence: 71%
“…Regarding absolute intensity, exercise test ended earlier under hypoxic than normoxic conditions (decrease of about 19.1%) as expected [4,27]. After adjusting the data to the last three exercise stages respectively for both conditions instead of regarding absolute intensity levels, heart rate, lactate concentration and ratings of perceived exertion did not differ between conditions.…”
Section: Heart Rate Lactate Concentration and Ratings Of Perceived Esupporting
confidence: 71%
“…1 A greater proportion of regions showing GM loss located in the limbic/paralimbic cortices in patients with COPD found in the present study may be due to the fact that those phylogenetically older regions of the brain showed sharper vascular responses to hypoxia than evolutionarily younger regions. 27 Although there is evidence that cigarette smoking may cause neuronal damage in the brains of patients with COPD, nicotine has no selective effect on some brain regions. In our study, we did not detect a correlation of the duration or the amount of smoking with the regional GM volume among all smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Although the brain is one of the most perfused organs in the body, the normal cerebral blood flow (CBF) is only 0.45 to 0.50 mL/g/min (0.0075-0.0083 mL/g/sec) (20)(21)(22), which is not sufficient to accomplish the fast washout nicotine from the brain and to sustain short-duration (tens of seconds) spikes in brain nicotine concentration. This conclusion can be illustrated by the following calculations.…”
Section: Cigarette Smokers Do Not Experience Puff-associated Spikes Imentioning
confidence: 99%